2010
DOI: 10.1021/jf100887v
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Variability of Antioxidative Phenolic Glycosides in Salix Species

Abstract: Phenolic glycosides, especially the salicylates, are important secondary metabolites in the bark of willows (Salix spp.). Because of their anti-inflammatory, analgesic, and fever-reducing properties, they are of particular interest to society. Compared to the fabrication of synthetic salicylacetylic acid, the commercial production of willow bark extracts with adequate amounts of salicylate is very difficult due to several biological and technical reasons. Therefore, one of the objectives was to identify salicy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 14 publications
(20 reference statements)
1
20
1
Order By: Relevance
“…The content of salicylates in the bark of S. myrsinifolia was higher in comparison to other herbal willows, such as S. purpurea , S. daphnoides , S. alba , and S. pentandra L. [5057]. In our study we also observed a higher level of phenolic compounds in the bark of willow S. myrsinifolia (23.10 mg/g DM) compared to the S. purpurea (20.04 mg/g DM).…”
Section: Resultssupporting
confidence: 60%
“…The content of salicylates in the bark of S. myrsinifolia was higher in comparison to other herbal willows, such as S. purpurea , S. daphnoides , S. alba , and S. pentandra L. [5057]. In our study we also observed a higher level of phenolic compounds in the bark of willow S. myrsinifolia (23.10 mg/g DM) compared to the S. purpurea (20.04 mg/g DM).…”
Section: Resultssupporting
confidence: 60%
“…Secondary metabolites mediate plant interactions with the environment and thus often undergo variable selection pressures across space and time, resulting in highly variable expression across plant genets (Lämke & Unsicker, ; Moore, Andrew, Külheim, & Foley, ). This broad pattern is seen in levels of salicinoids and condensed tannins in Salicaceae species, which can vary up to 10‐fold across genets grown in a common location (Boeckler et al., ; Förster, Ulrichs, Zander, Kätzel, & Mewis, ; Lindroth & St. Clair, ).…”
Section: Discussionmentioning
confidence: 99%
“…Symbols represent the generalized eta-squared (η 2 ) variation estimates, which were derived from models in Table 1 ( (Lämke & Unsicker, 2018;Moore, Andrew, Külheim, & Foley, 2014). This broad pattern is seen in levels of salicinoids and condensed tannins in Salicaceae species, which can vary up to 10-fold across genets grown in a common location (Boeckler et al, 2011;Förster, Ulrichs, Zander, Kätzel, & Mewis, 2010;Lindroth & St. Clair, 2013).…”
Section: Relative Effects Of G E and G×e Across Growth Phytochemimentioning
confidence: 99%
“…These variations could be ascribed to different part of the plant, polarity of solvent used for extraction, as well as environmental and growth conditions of the species. Moreover, secondary metabolite content in willows varies with season and time of the day, but also gender and age of the plant [33].…”
Section: Chemical Composition Of Bark and Leaves Extracts Of Various mentioning
confidence: 99%